Identification of lipopolysaccharide‐binding protein as a novel citrullinated autoantigen in rheumatoid arthritis. Issue 1 (24th January 2022) - Zhao, Xiaozhen; Chen, Yuling; Wen, Wen; Cheng, Yongjing; Li, Ru; Liu, Xu; Li, Yuhui; Jia, Rulin; Deng, Haiteng; Li, Zhanguo; Sun, Xiaolin
Abstract : We performed proteomic analysis by mass spectroscopy to identify novel citrullinated antigens and autoantibodies in RA patients. Graphical Abstract image see the attachment. Highlights: Serum protein analysis by high‐precision proteomic technology is a feasible method to identify novel citrullinated epitopes in RA patients. Anti‐cLBP antibodies are associated with disease severity and infection in RA patients. Abstract: Background: A specific feature of the autoimmune response in rheumatoid arthritis (RA) is the presence of anti‐citrullinated protein antibodies (ACPAs) in patient sera. These antibodies can appear several years before disease onset and are involved in the development of RA. Objective: We performed proteomic analysis by mass spectroscopy to identify novel citrullinated antigens and autoantibodies in RA patients. Methods: Polypeptides isolated from the sera of RA patients were identified by Orbitrap high‐precision mass spectrometry and then citrulline‐containing proteins were selected. The levels of ACPAs against these newly identified citrullinated autoantigens in sera of 100 RA patients and 50 healthy controls were determined by enzyme‐linked immunosorbent assays. Results: A total of 135 proteins were identified in RA patients and the protein profile included 11 citrulline‐containing antigens. Three of the 11 citrullinated proteins had been reported in previous studies. ACPAs against the novel citrullinated epitopes from these proteins were increased in sera from the RA patients compared with those from healthy controls. Autoantibodies against one of the citrullinated antigens, lipopolysaccharide‐binding protein (LBP), was significantly increased in RA patients and associated with disease activities. The titer of anti‐citrullinated LBP antibodies (anti‐cLBP) was closely related to the infection incidence in RA patients. Conclusion: Serum protein analysis by high‐precision proteomic technology is a feasible method to identify novel citrullinated epitopes in RA patients. Anti‐cLBP antibodies are associated with disease severity and infection in RA patients.